2021
DOI: 10.1002/advs.202100841
|View full text |Cite
|
Sign up to set email alerts
|

Mucin‐Like Glycoproteins Modulate Interfacial Properties of a Mimetic Ocular Epithelial Surface

Abstract: Dry eye disease (DED) has high personal and societal costs, but its pathology remains elusive due to intertwined biophysical and biochemical processes at the ocular surface. Specifically, mucin deficiency is reported in a subset of DED patients, but its effects on ocular interfacial properties remain unclear. Herein a novel in vitro mucin‐deficient mimetic ocular surface (Mu‐DeMOS) with a controllable amount of membrane‐tethered mucin molecules is developed to represent the diseased ocular surfaces. Contact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Our results corroborate those from other in vitro model systems of DED that incorporate human corneal and conjunctival cells, which showed that rh -lubricin increased tear film break up time and reduced the area of rupture. Although these systems can mimic the blinking motion of the eyelid to show that native lubricin (Seo et al ., 2019) and rh -lubricin 8 can decrease friction during blinking as well as investigate its immunomodulatory functions, our study complements these results by providing a cell-free way to visualize and quantify model tear film thickness, which is challenging in cell-based systems. As in this model, the absence of the outermost lipid layer can be a result of meibomian gland dysfunction, but the i-DDrOP is also compatible with deposition of lipid monolayers at the air–liquid interface.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our results corroborate those from other in vitro model systems of DED that incorporate human corneal and conjunctival cells, which showed that rh -lubricin increased tear film break up time and reduced the area of rupture. Although these systems can mimic the blinking motion of the eyelid to show that native lubricin (Seo et al ., 2019) and rh -lubricin 8 can decrease friction during blinking as well as investigate its immunomodulatory functions, our study complements these results by providing a cell-free way to visualize and quantify model tear film thickness, which is challenging in cell-based systems. As in this model, the absence of the outermost lipid layer can be a result of meibomian gland dysfunction, but the i-DDrOP is also compatible with deposition of lipid monolayers at the air–liquid interface.…”
Section: Discussionmentioning
confidence: 58%
“…One molecule that has shown promise, however, is recombinant human lubricin ( rh -lubricin), a mucin-like glycoprotein expressed by ocular surface epithelia as a product of the proteoglycan 4 (PRG4) gene. 6 Lubricin has been shown to significantly reduce shear stress and friction during blink cycles 6 8 and demonstrated a significant improvement in DED symptoms in a randomized clinical trial when compared with sodium hyaluronate eye drops. 9 The structure of rh -lubricin is shown in Figure 1 B.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Our results suggest that mucin presentation in our acellular in vitro model can be tuned simply by incubation with different concentrations of biotinylated BSM and streptavidin complex. While methods have been successfully developed to tune mucin presentation on corneal epithelial cells, 16 our method ensures compatibility with interferometry on the i-DDrOP by maintaining an optically smooth surface. This feature enables us to monitor the thickness of the liquid film over time on a curved substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The human eye, as well as in vitro models that incorporate cells, are subject to more factors including the presence of additional biomolecules and tear film components, cell signaling, movement, blinking, and gravity oriented in a different direction. Cell-based models also have the additional features of surface roughness that affect wettability, which render interferometry-based measurements more difficult. We also emphasize that our interpretation relies on the ability to distinguish film thickness through interferometry and that more advanced techniques such as hyperspectral imaging may be incorporated to more robustly quantify film thicknesses .…”
Section: Discussionmentioning
confidence: 99%
“…Immortalized human conjunctival and corneal epithelial cell lines capable of reproducibly differentiating into physiological, stratified cellular layers that retain the mucin expression patterns of native tissues represent a promising alternative to human tissues for high-throughput drug screening studies. We previously reported the development of an in vitro mucin-deficient DED model employing these cell lines in a live cell rheometer (LCR) setup to mimic complex ocular interface interactions . The mucin-deficient mimetic ocular surface (Mu-DeMOS) model recapitulates the frictional damage observed in mucin-deficient DED patients.…”
Section: Introductionmentioning
confidence: 99%